EXAMINATION ETHICS AND EXAMINATION MALPRACTICE: IMPLICATION FOR QUALITY EDUCATION - Kaura, Bello Ladan (Sokoto Educational Review, 2020)
Examination is a popular concept in Nigerian School System. It is well articulated in the process of teaching and learning from nursery stage to University level in Nigerian Education System. The chance of moving forward from lower to upper level is measured by the performance of Students in examination. Thus, the thrust of the paper is Examination Ethics and Examination Malpractice. The paper provides adequate Statistical record of annual Examination Malpractice from 1996-2005 base on geopolitical Zones, States and Zonal levels. Moreover, the paper identifies and explains the form s and causes of examination malpractice. Finally, in order to curb Examination Malpractice and ensure strict Examination Ethics, the students, teachers, parents, Examinees, Counsellors and the Society are recommended in the paper %o undertake certain drastic measures individually and collectively.